Attitudes and Health Behavior of Lawyers in Coimbatore, Tamil Nadu - G. Barani; Pavithra Sabapathy (The Scientific World Journal)
The aim of the study is to evaluate the differences in the behavior and attitudes of male and female lawyers regarding their lifestyles and health habits. Lawyers were randomly chosen. Data was obtained through a structured questionnaire distributed among the lawyers of Coimbatore district, Tamil Nadu. Lawyers are found to have unfavorable health practices related to use of tobacco and alcohol, exercise, diet, sleeping habits, and stress. This resulted in obesity, depression, and blood pressure. Many lawyers reported use of alcohol regularly, even as often as every day, and nearly half of them smoked. Many of the lawyers had poor feeding habit of skipping meals and eating snacks as breakfast. Most lawyers considered stressful situations to be unavoidable. Thus identifying individual lawyers with poor health behaviors and providing medical help are essential.